2019
DOI: 10.1016/j.bbamem.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of UL49.5 transmembrane protein from bovine herpesvirus 1 by NMR spectroscopy and molecular dynamics

Abstract: A B S T R A C TThe transporter associated with antigen processing (TAP) directly participates in the immune response as a key component of the cytosolic peptide to major histocompatibility complex (MHC) class I protein loading machinery. This makes TAP an important target for viruses avoiding recognition by CD8+ T lymphocytes. Its activity can be suppressed by the UL49.5 protein produced by bovine herpesvirus 1, although the mechanism of this inhibition has not been understood so far.Therefore, the main goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…In biological studies, it has been observed that the deletion of these three amino acid residues in the protein leads to a loss of transporting properties. We found the RRE residues in an α‐helix (fragment R9–A19 in the native protein) of our structural model, [11] and it is likely that the presence of this helix plays a role in the inhibition of antigenic peptide transport through the TAP channel. To verify this hypothesis, we designed and synthesized three peptide analogs with a modified RRE sequence.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In biological studies, it has been observed that the deletion of these three amino acid residues in the protein leads to a loss of transporting properties. We found the RRE residues in an α‐helix (fragment R9–A19 in the native protein) of our structural model, [11] and it is likely that the presence of this helix plays a role in the inhibition of antigenic peptide transport through the TAP channel. To verify this hypothesis, we designed and synthesized three peptide analogs with a modified RRE sequence.…”
Section: Introductionmentioning
confidence: 76%
“…This means that the studied peptides adopt one dominant conformation in the (1–27) fragment, while the C‐terminal fragment of the analogs is characterized by greater mobility. The increased mobility of the C‐terminal fragment (as in the case of the native BoHV peptide [11] ) may result from the presence of two proline residues in positions 31 and 32 or from cis‐trans isomerism. The chemical shifts of the protons of these residues in the studied analogs are very similar and their difference does not exceed ±0.25 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Designing an optimal fluorescent TAP construct was hampered by the lack of complete structural information about TAP-UL49.5 interaction, and thus, it required an experimental evaluation of different TAP-GFP variants. The latest structural study on BoHV-1 UL49.5 revealed its 3D structure, while subsequent molecular docking experiments proposed three different possible orientations of TAP-UL49.5 complex in which UL49.5 was suggested to interact simultaneously with both TAP subunits [44]. However, these models were predicted based on the structure of ICP47-arrested TAP conformation [10], and therefore the actual UL45.9-TAP binding model needs to be further confirmed.…”
Section: Discussionmentioning
confidence: 98%